Working deeply : transforming lives through transformational coaching - Barner, Robert; Ideus, Ken (Emerald Publishing Limited, 2017)
Coaching serves as a catalyst for supporting clients in their self-exploration and personal growth. In many instances, that growth has the potential to be transformational. Working Deeply is a guide for executive coaches and leadership development professionals to help them foster their clients' efforts in deep transformational learning. To facilitate this process, the authors introduce theories, concepts, and applied techniques for undertaking transformational coaching, and provide coaching cases and examples illustrating the use of these tools. They also introduce readers to a variety of research studies on such topics as mindfulness, mindsets, future selves, and narrative analysis, and discuss the application of this research to the area of transformational coaching. Finally, they explore how coaches can shape their perspectives and approaches to enable positive transformation. What readers will take from Working Deeply something of value that will help them develop their ability to support their coaching clients, and strengthen their practice as coaching professionals.
Keywords: Personal coaching.; Business & Economics -- Human Resources & Personnel Management.; Organizational theory & behaviour.; elektronické knihy; electronic books